Auditoría al Macroproceso de Proyección Social durante el primer semestre se 2012 (2012)
the present report contains the auditing of compliance to the macro process of social projection, which is fulfilled by the office of internal control, this covers a series of procedures with which is looked to guarantee the appropriate use of the resources of the activities; this way revising the accounting and financial part of the continued education of the university of quindio. to corroborate that the information presented by the faculties is trustworthy and transparent a type of study of description is contended, due to the fact that it is necessary to identify the operations that are achieved by each activity of continued education, with sustenance of the above mentioned the auditing group can emita a certified concept of the financial information and grade the internal control.